A review of toxicity induced by persistent organic pollutants (POPs) and endocrine-disrupting chemicals (EDCs) in the nematode Caenorhabditis elegans. (1st May 2019) - Chen, Haibo; Wang, Chen; Li, Hui; Ma, Ruixue; Yu, Ziling; Li, Liangzhong; Xiang, Mingdeng; Chen, Xichao; Hua, Xin; Yu, Yunjiang
Abstract: Persistent organic pollutants (POPs) and endocrine disrupting compounds (EDCs) are almost ubiquitous in synthetic and natural sources; however these contaminants adversely impact ecosystems and humans. Owing to their potential toxicity, concerns have been raised about the effects of POPs and EDCs on ecological and human health. Therefore, toxicity evaluation and mechanisms actions of these contaminants are of great interest. The nematode Caenorhabditis elegans ( C. elegans ), an excellent model animal for environmental toxicology research, has been used widely for toxicity studies of POPs or EDCs from the whole-animal level to the single-cell level. In this review, we have discussed the toxicity of specific POPs or EDCs after acute, chronic, and multigenerational exposure in C. elegans . We have also introduced a discussion of the toxicological mechanisms of these compounds in C. elegans, with respect to oxidative stress, cell apoptosis, and the insulin/IGF-1 signaling pathway. Finally, we raised considered the perspectives and challenges of the toxicity assessments, multigenerational toxicity, and toxicological mechanisms. Graphical abstract: Image 1081432 Highlights: Discussion of POPs and EDCs toxicity to C. elegans following different exposures. Introduction to mechanisms of toxicity of POPs and EDCs in C. elegans. Various perspectives and challenges were raised.